EITHER MANUFACTURING SECTOR RELY ON CAPITAL MARKETS ON THE BASIS OF FINANCIAL RESOURCES: AN EMPIRICAL STUDY OF INDUSTRIES IN PAKISTAN - Bazmi, Nisar Ahmad; Amir, Muhammad (International Journal For Research In Business, Management And Accounting, 2021)
The present study employed the financial resources of the manufacturing sector in Pakistan was to discover compare the performance of the manufacturing sector in Pakistan. Pakistan manufacturing sector find out effect on the performance of financial resources. Capital market firms, public financing, reallocation of internal resources, commercial financing and venture capital use various sources of finance, funds Market bonds and shares. According to (Dai, Jo, & Kassicieh, 2013; Gallagher, 2012) Relied on the release of Commercial financing, funding for these mostly companies rely on financial institutions. Few companies also use their own funds in the absence of public finances as well as companies also funding and venture capital reallocation of resources to their own use. This funding cost, magnitude of the risk associated with these resources due to their cost has a direct effect on the performance of firms that is clear. The present study used financial resources are manufacturing firms and their effect on the performance of this funding has been conducted to explore.